2006
DOI: 10.1136/jnnp.2006.087577
|View full text |Cite
|
Sign up to set email alerts
|

Primary sciatic nerve lymphoma: a case report and review of the literature

Abstract: A patient with primary B cell non-Hodgkin's lymphoma of the sciatic nerve is described. He presented with neuropathic symptoms in the left leg, initially diagnosed as tarsal tunnel syndrome. Magnetic resonance imaging (MRI) identified the abnormality in the sciatic nerve. A fascicular biopsy of the sciatic nerve showed a diffuse large B cell non-Hodgkin's lymphoma. The patient was treated with chemotherapy and rituximab (anti-CD20 monoclonal antibody). Four months later he was in remission, and remains so 48 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 13 publications
(8 reference statements)
2
40
1
1
Order By: Relevance
“…Similar to a description by Descamps et al, 8 MRI of this patient revealed a contrast-enhancing edematous lesion of the sciatic nerve that resembled a perineurioma or amyloidoma. Intraoperative findings and iHRU revealed a unique pathology, well distinguishable from that of all other tumor entities.…”
Section: Group B (Dense Giant Fascicles)supporting
confidence: 59%
See 1 more Smart Citation
“…Similar to a description by Descamps et al, 8 MRI of this patient revealed a contrast-enhancing edematous lesion of the sciatic nerve that resembled a perineurioma or amyloidoma. Intraoperative findings and iHRU revealed a unique pathology, well distinguishable from that of all other tumor entities.…”
Section: Group B (Dense Giant Fascicles)supporting
confidence: 59%
“…Other extremely rare nerve tumors or tumorlike lesions, such as perineurioma, amyloidoma, lymphoma, 4,7,8,18 and multifocal acquired demyelinating sensory and motor neuropathy (MADSAM), are even harder to distinguish preoperatively.…”
mentioning
confidence: 99%
“…Lymphoma can present as a mononeuropathy [7,8] with no other apparent disease [20]. On MRI the nerve often appears mildly enlarged with an irregular to nodular appearance, mild to moderate hyperintensity on T2-weighted sequences, and mild enhancement of the entire nerve [20].…”
Section: Discussion and Treatmentmentioning
confidence: 99%
“…On MRI the nerve often appears mildly enlarged with an irregular to nodular appearance, mild to moderate hyperintensity on T2-weighted sequences, and mild enhancement of the entire nerve [20]. The diagnosis was excluded when hematoxylin and eosin-stained biopsy sections did not show the large, pleomorphic, and mitotically active lymphoid cells seen with lymphoma [7,8].…”
Section: Discussion and Treatmentmentioning
confidence: 99%
“…Our case was an NK/T-cell subtype of lymphoma. The response of these lymphomas to treatment is variable (10). Various treatment approaches have been applied, including chemotherapy, radiotherapy, and surgery, alone and in various combinations (11).…”
Section: Discussionmentioning
confidence: 99%